2012
DOI: 10.1007/s00128-012-0547-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Imidacloprid in Chrysanthemi Flos and Soil

Abstract: Degradation of imidacloprid in chrysanthemi flos and cultivated soil was studied. The half-lives of imidacloprid were 3.55-5.17 days (soil), 2.10-3.98 days (fresh buds and flowers), 22.14 days (dry flowers, 5°C) and 13.08 days (dry flower, 20°C), separately. The temperature can affect imidacloprid degradation in soil and dry chrysanthemum buds and flowers. Imidacloprid residues in chrysanthemum flowers were more stable during store stage than growing one. Few imidacloprid residues would be dissolved into chrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The imidacloprid solution was then transferred in its entirety to a 50 mL cylindrical beaker and subjected to reduction using sponge iron (excess during degradation) in acidic conditions. Temperature has obvious effects on pesticide degradation (Ma et al, 2012;Wu et al, 2012), therefore, the degradation experiment was carried out in a cylindrical single-compartment where the reactor was externally immersed in water to keep the reaction at a constant temperature of 20 6 2 8C. This ensured the reduction degradation was performed at, approximately, ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The imidacloprid solution was then transferred in its entirety to a 50 mL cylindrical beaker and subjected to reduction using sponge iron (excess during degradation) in acidic conditions. Temperature has obvious effects on pesticide degradation (Ma et al, 2012;Wu et al, 2012), therefore, the degradation experiment was carried out in a cylindrical single-compartment where the reactor was externally immersed in water to keep the reaction at a constant temperature of 20 6 2 8C. This ensured the reduction degradation was performed at, approximately, ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental Protection Agency placed imidacloprid in category I as having the highest leaching potential [7]. Degradation of imidacloprid in chrysanthemi flos and cultivated soil was also studied by Wu et al [8]. The half-lives of imidacloprid were 3.55-5.17 days in soil, 2.10-3.98 days in fresh buds and flowers, 22.14 days in dry flowers at 5°C and 13.08 days in dry flower at 20°C.…”
Section: Introductionmentioning
confidence: 97%
“…14 IMDA is characterized by variable persistence in soil, with a half-life up to 229 days in the field. 18 In contrast, Wu et al 19 found under laboratory conditions that the degradation of IMDA was rapid, with half-lives of 4−5 days. The persistence of IMDA in water increased with increasing application rates and pH values.…”
Section: ■ Introductionmentioning
confidence: 97%